VLF radio engineering - Watt, Arthur D. (International series of monographs on electromagnetic waves, 1967)
Electromagnetic Waves, Volume 14: VLF Radio Engineering provides a detailed coverage of the fields involved in very low frequency (VLF) radio engineering. This book serves as a guide for applying the information in the solution of practical problems. Comprised of seven chapters, this volume starts with an overview of the communications aspect following the flow of information carrying energy from the transmitting to receiving locations. This text then presents the complete systems that consider the interrelationship of the various factors. Other chapters explain the basic concept of a VLF ante.